Інформаційне забезпечення адвокатського провадження у кримінальній справі - Рокітовська, Агнєшка; Марковець, Олександр (Видавництво Львівської політехніки, 2012)
This article is devoted to documents that the lawyer uses in the proceedings of a criminal case. In particular, the introduction of new actions to improve and accelerate the process of documenting and storing legal information, as the correct and systematic storage of legal documents depends on how effectively and quickly to run the task facing law firms.
Keywords: адвокатське провадження; спеціальне ПЗ; нормативно-правові акти